Glucoregulatory disruption in male mice offspring induced by maternal transfer of endocrine disrupting brominated flame retardants in DE-71 - Kozlova, Elena V.; Chinthirla, Bhuvaneswari D.; Bishay, Anthony E.; Pérez, Pedro A.; Denys, Maximillian E.; Krum, Julia M.; DiPatrizio, Nicholas V.; Currás-Collazo, Margarita C. (Frontiers in Endocrinology, 2023)
Polybrominated diphenyl ethers (PBDEs) are commercially used as indoor flame retardants that penetrate biota and bioaccumulate in human tissues, including breast milk. PBDEs have been associated with endocrine disruption, diabetes and metabolic syndrome (MetS) in humans and animals. However, their sex-specific diabetogenic effects are not completely understood. Our past works show diabetogenic effects of the commercial penta-mixture of PBDEs, DE-71, in perinatally exposed C57Bl/6 female mice. As a comparison, in the current study, the effects of DE-71 on glucose homeostasis in male offspring were examined. C57BL/6 dams were exposed to DE-71 at 0.1 mg/kg/d (L-DE-71), 0.4 mg/kg/d (H-DE-71) or received corn oil vehicle (VEH/CON) for a total of 10 wks, including gestation and lactation. Male offspring were examined in adulthood and DE-71 exposure produced hypoglycemia upon extended fasting. In vivo glucose challenge testing showed marked intolerance (H-DE-71) and incomplete clearance (L- and H-DE-71). Moreover, L-DE-71-exposed mice showed altered glucose responses to insulin, especially incomplete glucose clearance and/or utilization. In addition, L-DE-71 produced elevated levels of plasma glucagon and the incretin GLP-1 but no changes were detected on insulin. These alterations, which represent relevant criteria used clinically to diagnose diabetes, were accompanied with reduced hepatic glutamate dehydrogenase enzymatic activity, elevated adrenal epinephrine and decreased thermogenic brown adipose tissue mass, which may indicate several organ system targets of PBDEs. Liver levels of several endocannabinoid species were not altered by perinatal exposure to DE-71 in males. Our findings demonstrate that chronic low exposure to PBDEs in mothers can reprogram glucose homeostasis and glucoregulatory hormones in male offspring. Previous findings using female offspring showed altered glucose homeostasis that aligned with a contrasting diabetogenic phenotype. We summarize the results of the current work generated in males in light of previous findings on females. Taken together, these findings, combined with our prior results, offer a comprehensive account of sex-dependent effects of maternally transferred environmentally relevant PBDEs on glucose homeostasis and glucoregulatory endocrine dysregulation.